Length-based stock assessment in small-scale multi-gear fisheries: insights from a European hotspot (NW Spain) - Daniel García-García; Marta Cousido-Rocha; Rafael Bañón; José Manuel Campelos; Fernando Quintero; Asunción Gancedo; Fabio Lamas; Alberto Otero; Angel Rodríguez; Alexandre Alonso-Fernández (Reviews in Fish Biology and Fisheries, 2026)

UV-VIS-NIR chemometric screening of broccoli by-products: Decoupling the spatiotemporal heterogeneity of glucosinolates and functional traits - Iris Gudiño; Jesús Alonso; Rocío Casquete; María José Benito; Santiago Ruiz-Moyano; Alberto Martín (Food Chemistry, 2026)

Urban land use and management drive soil pollution across urban and nearby natural ecosystems in the Iberian Peninsula - Andrea C. Sala-Navarro; Nuria Casado-Coy; Axel Campos-Castro; Camelia Algora; Elena Aguilar-Santana; Kaiyan Zhai; Josu G. Alday; Cristina Armas; C. Guillermo Bueno; Leonor Calvo; María Dolores Carmona-Yáñez; Giada Centenaro; et al. (Journal of Hazardous Materials, 2026)

Correction to: Rational design of lipid-based nanoparticles for targeted anticancer therapies - María Arenas‑Moreira; Alberto Ocaña; Carlos Alonso-Moreno; Iván Bravo (Drug Delivery and Translational Research, 2026)

Rational design of lipid-based nanoparticles for targeted anticancer therapies - María Arenas-Moreira; Alberto Ocaña; Carlos Alonso-Moreno; Iván Bravo (Drug Delivery and Translational Research, 2026)

Zoonotic Exposure to Kudoa Parasites (Myxosporea: Multivalvulida) in the Canary Islands (Macaronesia, Spain): Implications for Human Health and Immune Sensitization Associated with Seafood Consumption - Eligia González-Rodríguez; Marta Rodero; Sergio Llorens-Berzosa; J. Alberto Montoya-Alonso; Kevin M. Santana-Hernández; Myriam R. Ventura; Carmen Cuéllar; Eligia Rodríguez-Ponce (Acta Parasitologica, 2026)

Controlled synthesis of graphene oxide by electrochemical exfoliation for advanced nanofiltration membranes - Raul Pla; Daniel Fernandez-Carrasco; Silvia Villar-Rodil; Jose Alberto Baeza; Luisa Calvo; Noelia Alonso-Morales; Miguel Angel Gilarranz; Fabian Suarez-García; Juan Ignacio Paredes (Journal of Environmental Chemical Engineering, 2026)

Impacts of aqueous extracts of tree leaves on the aquatic snail Potamopyrgus antipodarum: exploring the roles of leaf habit and geographic origin - Alberto Romero-Blanco; Paula Cruces; Celeste Llandres; Beatriz R. Vázquez-de-Aldana; Virginia O. González-Blanco; Pilar Castro-Díez; Álvaro Alonso (Aquatic Ecology, 2026)
The introduction of exotic tree species with dissimilar leaf habits or distinctive chemical composition into native communities may cause impacts on aquatic organisms, yet the relative influence of leaf habit and geographic origin on those impacts remain poorly understood. In this study, we experimentally explored the ecotoxicological effects of aqueous leaf litter extracts from 15 tree species differing in leaf habit (deciduous vs evergreen) and geographic origin (exotics vs natives in Spain) on the mortality and behavior of the aquatic snail Potamopyrgus antipodarum (Gray, 1843). Snails were exposed for 7 days to three leaf extract concentrations of each tree species. No mortality effects were observed at any concentration. In contrast, the behavioral responses of snails were negatively affected at the highest concentration, showing increased reaction time and reduced speed. These responses were species-specific and associated with leaf habit and chemical composition of extracts rather than geographic origin. Leaf extracts from deciduous trees caused a greater slowing down of snails than extracts from evergreen trees. Overall, our results indicate that leaf litter impacts on Potamopyrgus antiporadrum depend more on tree species identity and leaf habit than on native or exotic status, highlighting the importance of leaf traits when assessing ecotoxicological risks in freshwater ecosystems.

Correction: Anti-inflammatory, antioxidant, and antinociceptive properties of methanolic flower extracts of Tecoma stans: a promising natural therapeutic agent - Abril Bernardette Martínez-Rizo; Oscar Isaac Correa-Polanco; Valeria García-Martínez; Fabiola Villa-de la Torre; Mario Alberto Ramírez-Camacho; Rocio Borges-Argáez; Eunice Yáñez-Barrientos; Alan Alexander Gonzalez-Ibarra; Angel Josabad Alonso-Castro; Claribel Huchin Chan; Victor Ermilo Arana-Argáez (Inflammopharmacology, 2026)

Assessment of monthly infection risk of heartworm infection in Colombia: integrative ecological niche modeling of Culex quinquefasciatus and Dirofilaria immitis - Rodrigo Morchón; Elena Infante González-Mohino; María Victoria Esteban-Mendoza; Manuel Collado-Cuadrado; Víctor Arcila-Quiceno; José Alberto Montoya-Alonso; Elena Carretón; Iván Rodríguez-Escolar (Veterinary Parasitology, 2026)

Assessing whale-watching compliance: A replicable framework for international–national correspondence in continental America - David Alonso Rosales-Chapula; César Augusto Salinas-Zavala; Marco Antonio Almendarez-Hernández; Cristina González-Rubio Sanvicente; José Alberto Zepeda-Domínguez; María Verónica Morales-Zárate (Regional Studies in Marine Science, 2026)

Pilot-scale demonstration of Ca–Cu looping for CO₂ capture from blast furnace gas - Jose Ramon Fernandez; Monica Alonso; Roberto Garcia; Alberto Mendez; Marcos Cano; Carlos Abanades (Chemical Engineering Journal, 2026)

Anti-inflammatory, antioxidant, and antinociceptive properties of methanolic flower extracts of Tecoma stans: a promising natural therapeutic agent - Abril Bernardette Martínez-Rizo; Oscar Isaac Correa-Polanco; Valeria García-Martínez; Fabiola Villa-de la Torre; Mario Alberto Ramírez-Camacho; Rocio Borges-Argáez; Eunice Yáñez-Barrientos; Alan Alexander Gonzalez-Ibarra; Angel Josabad Alonso-Castro; Claribel Huchin Chan; Victor Ermilo Arana-Argáez (Inflammopharmacology, 2026)

Removal of PFAS from complex matrix water by filtration with supported graphene oxide membranes - Raul Pla; Noelia Alonso-Morales; Jose Alberto Baeza; Luisa Calvo; Miguel Angel Gilarranz (Journal of Environmental Chemical Engineering, 2025)

Alarming conservation status of Western European steppe birds and their habitats: An expert-based review of current threats, traits and knowledge gaps - Julia Gómez-Catasús; Ana Benítez-López; Mario Díaz; David González del Portillo; Cristian Pérez-Granados; Juan Carlos Alonso; Beatriz Arroyo; Inmaculada Abril-Colón; Adrián Barrero; Rafael Barrientos; Luis Bolonio; Gerard Bota; et al. (Biological Conservation, 2025)

Acute caffeine intake improves muscular strength, power, and endurance performance, reversing the time-of-day effect regardless of muscle activation level in resistance-trained males: a randomized controlled trial - Juan Jesús Montalvo-Alonso; Marta del Val-Manzano; Ester Cerezo-Telléz; Carmen Ferragut; David Valadés; Javier Rodríguez-Falces; Alberto Pérez-López (European Journal of Applied Physiology, 2025)
Introduction This study examined the effects of acute caffeine intake on muscular electrical activity during strength, power, and endurance performance tests at different times of day in bench press and back squat exercises. Methods Thirteen resistance-trained men participated in a triple-blind, cross-over, randomized controlled trial with four conditions: (a) morning with caffeine, (b) morning with placebo, (c) evening with caffeine, and (d) evening with placebo. Trials were conducted at 9:00 AM and 6:00 PM, with participants consuming caffeine or placebo (3 mg/kg) 60 min prior. Muscular strength/power was tested at 25%, 50%, 75%, and 90% one-repetition maximum (1RM) for bench press and back squat, while muscular endurance was assessed at 65% 1RM through a set-to-failure. Surface electromyography (EMG) measured muscle electrical activity. Results In muscular strength/power tests, caffeine increased mean velocity (V mean ) and power output (W mean ) in the back squat at 75% (P = 0.012–0.001, g = 3.84–2.71) and 90%1RM (P = 0.043–0.009, g = 2.77–2.46) in both morning and evening trials. At 25%1RM, caffeine counteracts morning performance decline in bench press (10–11%, P = 0.001, g = 2.62–1.68) and back squat (8–11%, P = 0.010–0.003, g = 2.22–1.64). In muscular endurance tests, caffeine increased V mean and W mean in bench press in the morning (11–12%, P = 0.003–0.005, g = 2.55–1.89) and back squat in both morning and evening trials (6–9%, P = 0.001–0.027, g = 2.79–1.73). EMG activity remained unchanged in all conditions. Conclusions Acute caffeine intake enhances muscular strength/power at moderate-to-high loads (75%- 90%1RM) and endurance performance (65%1RM) in the back squat while counteracting morning declines at light-load (25%1RM) for both exercises without altering muscle electrical activity.

Enhancing the processability and mechanical performance of collagen-based biofilms through supercritical carbon dioxide plasticisation - Karina C. Núñez C.; Luis E. Alonso Pastor; Félix Lizalde-Arroyo; Jaime Lledó; Leandra Oliveira Salmazo; Alberto Lopez-Gil; Miguel A. Rodríguez-Pérez (Journal of Food Engineering, 2025)

Hyperthermia and Early Growth of Cerebral Infarct: The Potential Role of Blood–Brain Barrier Permeability - Crhistian-Mario Oblitas; Ana Sampedro-Viana; Sabela Fernández-Rodicio; Manuel Rodríguez-Yáñez; Iria López-Dequidt; Arturo Gonzalez-Quintela; Antonio J. Mosqueira; Jacobo Porto-Álvarez; Javier Martínez Fernández; Marcos Bazarra-Barreiros; María Teresa Abengoza-Bello; Sara Ortega-Espina; et al. (Translational Stroke Research, 2025)
Hyperthermia within the first 24 h following ischemic stroke (IS) has been associated with poor outcomes. We sought to determine whether blood–brain barrier (BBB) permeability contributes to the relationship between hyperthermia and early infarct growth (EIG). A retrospective analysis was conducted on a prospective stroke biobank. EIG was defined as the percentage difference between the initial volume (mL) determined by the diffusion-weighted imaging at admission and the volume (mL) from the control CT image on the 4 th–7 th day. Hyperthermia was defined as an axillary body temperature ≥ 37.5 °C within the first 24 h. Soluble tumor necrosis factor-like weak inducer of apoptosis (sTWEAK) serum levels were measured by ELISA. One-hundred and two (19.7%) patients showed EIG from a cohort of 519 patients (45.6% females). Linear correlation was observed for axillar body temperature and EIG (Pearson’s r = 0.46; p < 0.001). sTWEAK serum levels showed a c -statistic of 0.74 (95% CI: 0.69–0.79), with an optimal cut-off point > 3000 pg/mL for EIG prediction. Moreover, microalbuminuria levels strongly correlated with sTWEAK levels (Pearson’s r = 0.75; p < 0.001). In the multivariate analysis for EIG was observed an independent association with hyperthermia (adjusted OR 24.21; 95% CI: 12.03–39.12), sTWEAK levels > 3000 pg/mL (adjusted OR 16.43; 95% CI: 3.71–72.70), leukoaraiosis (adjusted OR 10.42; 95% CI: 2.68–39.08), and microalbuminuria (adjusted OR 1.02; 95% CI: 1.00–1.12). In our cohort, hyperthermia was independently associated with EIG after IS. The fact that microalbuminuria, leukoaraiosis, and sTWEAK were also associated with EIG suggests a relationship with increased BBB permeability.

Exploring the relationship of potential new rhizobacteria metabolism with Lotus spp. performance in a rice-pasture rotation system - Vanina Giselle Maguire; Andrés Alberto Rodríguez; Andrés Mariano Alonso; Juan Pedro Ezquiaga; Nehuén Salas; María Eugenia Llames; Maximiliano Gortari; Nicolás Ayub; Silvina Maricel Brambilla; Pedro José Bouilly; Fernando Matías Romero; Andrés Gárriz; et al. (Symbiosis, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Combining extrusion and hot compression molding for the development of bioplastics and nano-biocomposites based on rice bran - María Alonso-González; Manuel Felix; Alberto Romero; Eric Pollet (Journal of Food Engineering, 2025)

Innovative approaches to bioplastic development: rice bran/PLA blends via extrusion combined with injection molding and 3D printing - María Alonso-González; Manuel Felix; Alberto Romero; Laura Aliotta; Vito Gigante; Claudia Sergi; Irene Bavasso; Fabrizio Sarasini (Journal of Environmental Management, 2025)

Correction to: Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández‑Pérez; Joan Jiménez‑Balado; Adrià Macias‑Gómez; Antoni Suárez‑Pérez; Marta Vallverdú‑Prats; Alberto Pérez‑Giraldo; Marc Viles‑García; Julia Peris‑Subiza; Sergio Vidal‑Notari; Eva Giralt‑Steinhauer; Daniel Guisado‑Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

Blood DNA Methylation Analysis Reveals a Distinctive Epigenetic Signature of Vasospasm in Aneurysmal Subarachnoid Hemorrhage - Isabel Fernández-Pérez; Joan Jiménez-Balado; Adrià Macias-Gómez; Antoni Suárez‑Pérez; Marta Vallverdú-Prats; Alberto Pérez-Giraldo; Marc Viles-García; Julia Peris-Subiza; Sergio Vidal-Notari; Eva Giralt-Steinhauer; Daniel Guisado-Alonso; Manel Esteller; et al. (Translational Stroke Research, 2025)

Molecular study of vitamin D metabolism-related single nucleotide polymorphisms in cardiovascular risk: a case-control study - José María Gálvez-Navas; Noelia Márquez-Pete; Madalena Paiva-Chaves; Susana Rojo-Tolosa; Laura Elena Pineda-Lancheros; Yasmin Cura; Cristina Membrive-Jiménez; Luciana Maria Marangoni-Iglecias; Andrea Fernández-Alonso; MCarmen Ramírez-Tortosa; Cristina Pérez-Ramírez; Alberto Jiménez-Morales (Journal of Physiology and Biochemistry, 2025)
Cardiovascular diseases (CVDs) constitute a major global health problem, being the leading cause of death. Several risk factors for CVDs have been identified, including tobacco use, unhealthy diet, and physical inactivity. However, the role of genetic factors in CVDs remains unclear. Recent studies suggest that vitamin D deficiency is associated with an increased risk of CVDs. Therefore, the aim of this study is to assess the impact of 13 single nucleotide polymorphisms (SNPs) located in genes involved in vitamin D metabolism ( VDR , GC , CYP27B1 , CYP2R1 , and CYP24A1 ) on the risk of developing CVDs. A retrospective case-control study was conducted in 766 Caucasian individuals from southern Spain: 383 diagnosed with CVDs and 383 without cardiovascular complications, matched based on age and sex. The 13 SNPs were identified by real-time PCR using TaqMan™ probes at the Virgen de las Nieves University Hospital and the University of Granada. According to statistical analysis the allele G and genotype GG of the SNP CYP2R1 rs10741657 and the allele C and CC genotype of the SNP CYP27B1 rs3782130 are associated with a decreased risk of CVDs and diabetes in three of the five heritage models studied. Thus, it can be concluded that CYP2R1 rs10741657 and CYP27B1 rs3782130 could be used as risk biomarkers for CVDs in the future, although studies with a larger number of participants are needed.

Metagenomic surveys show a widespread diffusion of antibiotic resistance genes in a transect from urbanized to marine protected area - Tania Alonso-Vásquez; Camilla Fagorzi; Alessio Mengoni; Matteo Oliva; Duccio Cavalieri; Carlo Pretti; Lisa Cangioli; Giovanni Bacci; Alberto Ugolini (Marine Pollution Bulletin, 2025)

Periocular basal cell carcinoma in a donkey: case report - Juliana de Moura Alonso; Emanuel Vitor Pereira Apolonio; Fwu Shing Teng; Pyetra Ieger Perandré; Renee Laufer Amorim; Renata Dalcol Mazaro; Marcos Jun Watanabe; Ana Liz Garcia Alves; Carlos Alberto Hussni (Veterinary Research Communications, 2025)

Application of Artificial Intelligence in Identifying Human Immunoglobulin and Albumin in Commercial Intravenous Drugs - Juan Padierna-Olivos; Juan Francisco Sánchez-Ruiz; Gustavo Alonso Martínez-Blanco; Carlos Arturo Medina-García; Brenda Magali Lin-Li Lagunas-Bucio; Ariadna Rosas-Hernández; Cecilia Padierna-Mota; Alberto Padierna-Mota; Carlos Gershenson-García (Journal of Pharmaceutical Innovation, 2025)

Correction: Nest‑site and brood‑rearing habitat selection in Canarian houbara bustards: the importance of concealment and food availability - Alberto Ucero; Inmaculada Abril-Colón; Carlos Palacín; Jose Manuel Álvarez-Martínez; Juan Carlos Alonso (Journal of Ornithology, 2025)

Nest-site and brood-rearing habitat selection in Canarian houbara bustards: the importance of concealment and food availability - Alberto Ucero; Inmaculada Abril-Colón; Carlos Palacín; Jose Manuel Álvarez-Martínez; Juan Carlos Alonso (Journal of Ornithology, 2025)
Using two scales, landscape and microhabitat, we analysed the factors determining nest-site and brood-rearing habitat selection in the endangered Canarian Houbara Bustard Chlamydotis undulata fuertaventurae . We measured vegetation cover and food abundance, presence of human infrastructure, and visibility using a very high-resolution LiDAR-based digital elevation model of the terrain. Houbara females choose nest-sites with abundant arthropod biomass and high vegetation. To rear their brood, they look for substrates with few stones, high species richness, and low density of human infrastructure. These features allow females to hide the nest, themselves and their chicks from predators, reduce anthropogenic disturbance, and secure access to food during the whole breeding process. The less stony ground during brood-rearing allows female and chicks to walk more easily and safely, something that is important in a ground-dwelling bird. This study represents the first detailed analysis of nesting and breeding site selection for this globally threatened subspecies. To minimise disturbance during such a sensitive phase, and considering the major tourist destination in which this species lives, we recommend to restrict vehicle and human traffic in the breeding areas, prohibit new constructions in houbara habitats, and preserve the vegetation and breeding-habitat quality, avoiding the current indiscriminate ploughing of uncultivated fields and limiting goat grazing areas.

Green covers effectively increase arthropod biodiversity in orchards, even at high management intensity - Remco Ploeg; Alberto Rodriguez Ballesteros; Ignasi Bartomeus; David Kleijn; Jeroen Scheper; Elena Velado Alonso (Agriculture, Ecosystems & Environment, 2025)

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

A novel methodology for the characterisation of airflow using infrared thermography and pressurisation test - Diego Tamayo-Alonso; Alberto Meiss (Building and Environment, 2025)

Treatment of mycotic rhinitis caused by aspergillus fumigatus in a quarter horse mare using topical clotrimazole and oral potassium iodide - Juliana de Moura Alonso; Marcos Jun Watanabe; Sandra de Moraes Gimenes Bosco; Emanuel Vitor Pereira Apolonio; Artur Bibiano de Vasconcelos; Ana Carolina do Prado; Ana Liz Garcia Alves; Celso Antonio Rodrigues; Carlos Alberto Hussni (Veterinary Research Communications, 2025)

Lab-scale biocomposite manufacturing: Exploring rice bran-based bioplastics reinforced with natural fillers through extrusion and injection molding - María Alonso-González; Manuel Felix; Alberto Romero; Claudia Sergi; Irene Bavasso; Fabrizio Sarasini (Resources, Conservation and Recycling, 2025)

Argentina's rejection of 2030 agenda undermines environmental sustainability and human well-being - Javier Nori; Alejandro E.J. Valenzuela; Micaela Camino; Elena Abraham; Gabriela Agostini; Marcelo A. Aizen; Virginia Alonso-Roldán; Julieta R. Arcamone; Yanina Arzamendia; German Baldi; Diego Baldo; Matías C. Baranzelli; et al. (Biological Conservation, 2024)

One-pot, microwave (MW)-assisted production of furfural from almond-, oil-, and wine-derived co-products through biorefinery-based approaches - Manuel Salgado-Ramos; Alberto José Huertas-Alonso; Almudena Lorente; María Prado Sánchez-Verdú; Andrés Moreno; Beatriz Cabañas (Waste Management, 2024)

Development of rice bran-based bioplastics via injection molding: Influence of particle size and glycerol ratio - María Alonso-González; Manuel Felix; Alberto Romero (Resources, Conservation and Recycling, 2024)

Loss of amphibian species alters periphyton communities in montane ponds - Alberto Alonso; Jaime Bosch; Luz Boyero (Hydrobiologia, 2024)
Amphibian larvae can affect the structure and functioning of freshwater ecosystems, but their effects have been little explored although amphibian biodiversity is rapidly declining. Given that larvae of different amphibian species belong to different trophic levels, their effects on freshwater communities and processes can be expected to differ, with herbivores likely having direct effects on algae and predators having indirect effects through trophic cascades. We explored this question through a mesocosm experiment conducted in montane ponds, using an anuran and a urodele species affected by emergent diseases. We used different scenarios of reduction and loss of one or both species, and compared them to a control scenario representing a typical amphibian community in the study area composed of four species, with total larval density held constant. Loss of the anuran resulted in lower chlorophyll concentration and algal density, likely due to replacement by more efficient grazers. Loss of the urodele produced similar trends but weaker, possibly due to an increase of invertebrate grazing activity in the absence of this predator. Our study shows how the loss of amphibian species can alter the structure of montane ponds, but also how the mechanisms involved and the intensity of effects differ for different species.

The COVID19 confinement revealed negative anthropogenic effects of unsustainable tourism on endangered birds - Inmaculada Abril-Colón; Carlos Palacín; Alberto Ucero; Juan Carlos Alonso (Biological Conservation, 2024)

Trihalomethane Levels in Municipal Drinking Water of Madrid (Spain) and Health Risk Assessment for Oral Exposure - Mª Concepción Almonacid Garrido; Mª José Villanueva-Suárez; Alberto Álamo Gómez; Alejandra Garcia-Alonso; Mª Dolores Tenorio Sanz (Exposure and Health, 2024)
Trihalomethanes (THMs) are generated in the drinking water treatment plant, due to the reaction of the halogenated disinfection compounds with the natural organic matter (NOM). They are related to health problems both from the point of view of cancer development and other important diseases. This study aimed to assess the quality of tap water in Madrid in terms of prevention and control of THMs risks in the supply water treated by Canal de Isabel II (CYII) in a total of 108 samples throughout 2015 to 2020, to distinguish the problems of the different 21 districts or types of buildings, the seasonality and to estimate the risk of exposure to THMs from tap water in the population of Madrid. The variables considered include year, seasonality, district of Madrid and sampling point. The concentrations of THMs detected in all samples were within the current legal limit (100 µg/l). Chloroform was the compound with the highest contribution to the sum of THMs. A decreasing trend in THMs concentrations was observed over the years of the study related to the removal of NOM and the use of chloramines. THM levels were higher in the central area than in the peripheral districts and the lowest concentrations were detected in summer. Regarding risk assessment, the results of the non-carcinogenic risk indicate that there is no potential risk from tap water consumption for the adult population. For the carcinogenic risk, only water samples with THM concentrations between 50 and 75 µg/l could constitute a risk for high consumers.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Exposure to environmental pollutants and genetic variants related to oxidative stress and xenobiotic metabolism—Association with prostate cancer - Beatriz Álvarez-González; Antonio F. Hernández; Alberto Zafra-Gómez; Lucia Chica-Redecillas; Sergio Cuenca-López; Fernando Vázquez-Alonso; Luis Javier Martínez-González; María Jesús Álvarez-Cubero (Environmental Toxicology and Pharmacology, 2024)

Joint effects of warming and salinization on instream leaf litter decomposition assessed through a microcosm experiment - Gabriela García; Javier Pérez; Luz Boyero; Alberto Alonso; Anyi Tuñon; Edgar Pérez; Aydeé Cornejo (Hydrobiologia, 2024)
Stream ecosystem functioning is often impaired by warming and salinization, but the joint effect of both environmental stressors on key processes such as leaf litter decomposition is virtually unknown, particularly in the tropics. We experimentally explored how increased water temperature (26, 29 and 32°C) and salinity (no salt addition, 0.1, 1.0 and 10 g l −1 NaCl added) affected the rates of total, microbial and detritivore-mediated decomposition, in stream microcosms containing leaf litter of Ficus insipida and larvae of Chironomus sp. collected from tropical streams. Effects of temperature were strong and consistent with previous findings: it promoted microbial decomposition and reduced decomposition mediated by detritivores, which showed greater feeding activity at 26°C. Salinity was negatively correlated with microbial decomposition at 32°C; it also had a negative influence on detritivore-mediated decomposition, which was nevertheless non-significant due to the high detritivore mortality at higher salinities. Notably, total decomposition was reduced with the joint presence of both factors (32°C and salt addition treatments, compared to 26°C and no salt addition), indicating the existence of additive effects and highlighting the relevance of multiple-stressor contexts when assessing the consequences of global change on stream ecosystems.

The FOODRUS index: Assessing suitability for effective food loss and waste prevention management under an integral perspective - Manuel Amador-Cervera; Juan S. Angarita-Zapata; Alberto de la Calle Vicente; Ainhoa Alonso-Vicario (Waste Management, 2024)

Regional assessment of the historical trends of mercury in sediment cores from Wider Caribbean coastal environments - Yoelvis Bolaños-Alvarez; Ana Carolina Ruiz-Fernández; Joan-Albert Sanchez-Cabeza; Misael Díaz Asencio; Luisa F. Espinosa; Juan Pablo Parra; Jesús Garay; Ramón Delanoy; Nicolás Solares; Katia Montenegro; Alexis Peña; Fabiola López; et al. (Science of The Total Environment, 2024)

Sediment source fingerprints of natural processes and anthropogenic pressures: A contribution to manage the Paraopeba River basin impacted by the B1 tailings dam collapse - Carolina Acuna-Alonso; Renato Farias do Valle Junior; Mayte Maria Abreu Pires de Melo Silva; Teresa Cristina Tarlé Pissarra; Marília Carvalho de Melo; Carlos Alberto Valera; Luis Filipe Sanches Fernandes; Fernando António Leal Pacheco; Xana Álvarez (Journal of Environmental Management, 2024)

Sustainable management of wine-derived leftovers: Enhanced extraction of antioxidants and production of levulinic acid by microwave-assisted processing - Manuel Salgado-Ramos; Alberto J. Huertas-Alonso; Francisco J. Martí-Quijal; Francisco J. Barba; M. Prado Sánchez-Verdú; Andrés Moreno; Beatriz Cabañas (Journal of Environmental Chemical Engineering, 2024)

The role of automatic pollen and fungal spore monitoring across major end-user domains - Fiona Tummon; Beverley Adams-Groom; Célia M. Antunes; Nicolas Bruffaerts; Jeroen Buters; Paloma Cariñanos; Sevcan Celenk; Marie Choël; Bernard Clot; Antonella Cristofori; Benoît Crouzy; Athanasios Damialis; et al. (Aerobiologia, 2024)
The advent of automatic pollen and fungal spore monitoring over the past few years has brought about a paradigm change. The provision of real-time information at high temporal resolution opens the door to a wide range of improvements in terms of the products and services made available to a widening range of end-users and stakeholders. As technology and methods mature, it is essential to properly quantify the impact automatic monitoring has on the different end-user domains to better understand the real long-term benefits to society. In this paper, we focus the main domains where such impacts are expected, using Europe as a basis to provide qualitative estimates and to describe research needs to better quantify impacts in future. This will, in part, also serve to justify further investment and help to expand monitoring networks.

Impact of wildfire ash on bacterioplankton abundance and community composition in a coastal embayment (Ría de Vigo, NW Spain) - Alberto Gutiérrez-Barral; Eva Teira; Alexandra Díaz-Alonso; Maider Justel-Díez; Joeri Kaal; Emilio Fernández (Marine Environmental Research, 2024)

Winemaking-derived by-products: In-depth characterization and sustainable, advanced pulsed electric field (PEF) processing to a zero-waste-based approach - Manuel Salgado-Ramos; Francisco J. Martí-Quijal; Alberto J. Huertas-Alonso; M. Prado Sánchez-Verdú; Andrés Moreno; Francisco J. Barba (Journal of Environmental Chemical Engineering, 2023)

Uptake and depuration of three common antibiotics in benthic organisms: Sea cucumber (Holothuria tubulosa), snakelocks anemone (Anemonia sulcata) and beadlet anemone (Actinia equina) - María del Carmen Gómez-Regalado; Julia Martín; Felix Hidalgo; Juan Luis Santos; Irene Aparicio; Esteban Alonso; Alberto Zafra-Gómez (Environmental Research, 2023)

Warming overrides eutrophication effects on leaf litter decomposition in stream microcosms - Javier Pérez; Aydeé Cornejo; Alberto Alonso; Alisson Guerra; Gabriela García; Carlos Nieto; Francisco Correa-Araneda; Diana Rojo; Luz Boyero (Environmental Pollution, 2023)

Accumulation and metabolization of the antidepressant venlafaxine and its main metabolite o-desmethylvenlafaxine in non-target marine organisms Holothuria tubulosa, Anemonia sulcata and Actinia equina - María del Carmen Gómez-Regalado; Julia Martín; Felix Hidalgo; Juan Luis Santos; Irene Aparicio; Esteban Alonso; Alberto Zafra-Gómez (Marine Pollution Bulletin, 2023)

Involvement of the excretory/secretory and surface-associated antigens of Dirofilaria immitis adult worms in the angiogenic response in an in-vitro endothelial cell model - Cristian David Cardona Machado; Claudia Alarcón-Torrecillas; Miguel Pericacho; Iván Rodríguez-Escolar; Elena Carretón; José Alberto Montoya-Alonso; Rodrigo Morchón (Veterinary Parasitology, 2023)

Bioconcentration of pharmaceuticals in benthic marine organisms (Holothuria tubulosa, Anemonia sulcata and Actinia equina) exposed to environmental contamination by atenolol and carbamazepine - María del Carmen Gómez-Regalado; Julia Martín; Felix Hidalgo; Juan Luis Santos; Irene Aparicio; Esteban Alonso; Alberto Zafra-Gómez (Environmental Toxicology and Pharmacology, 2023)

Inputs of seabird guano alter microbial growth, community composition and the phytoplankton–bacterial interactions in a coastal system - Maider Justel‐Díez; Erick Delgadillo‐Nuño; Alberto Gutiérrez‐Barral; Paula García‐Otero; Isaac Alonso‐Barciela; Pablo Pereira‐Villanueva; Xosé Antón Álvarez‐Salgado; Alberto Velando; Eva Teira; Emilio Fernández (Environmental Microbiology, 2023)
Seabird guano enters coastal waters providing bioavailable substrates for microbial plankton, but their role in marine ecosystem functioning remains poorly understood. Two concentrations of the water soluble fraction (WSF) of gull guano were added to different natural microbial communities collected in surface waters from the Ría de Vigo (NW Spain) in spring, summer, and winter. Samples were incubated with or without antibiotics (to block bacterial activity) to test whether gull guano stimulated phytoplankton and bacterial growth, caused changes in taxonomic composition, and altered phytoplankton–bacteria interactions. Alteromonadales, Sphingobacteriales, Verrucomicrobia and diatoms were generally stimulated by guano. Chlorophyll a (Chl a ) concentration and bacterial abundance significantly increased after additions independently of the initial ambient nutrient concentrations. Our study demonstrates, for the first time, that the addition of guano altered the phytoplankton–bacteria interaction index from neutral (i.e. phytoplankton growth was not affected by bacterial activity) to positive (i.e. phytoplankton growth was stimulated by bacterial activity) in the low‐nutrient environment occurring in spring. In contrast, when environmental nutrient concentrations were high, the interaction index changed from positive to neutral after guano additions, suggesting the presence of some secondary metabolite in the guano that is needed for phytoplankton growth, which would otherwise be supplied by bacteria.

Sequential extraction of almond hull biomass with pulsed electric fields (PEF) and supercritical CO2 for the recovery of lipids, carbohydrates and antioxidants - Manuel Salgado-Ramos; Francisco J. Martí-Quijal; Alberto J. Huertas-Alonso; M. Prado Sánchez-Verdú; Giancarlo Cravotto; Andrés Moreno; Francisco J. Barba (Food and Bioproducts Processing, 2023)

Tree-size heterogeneity modulates the forest age-dependent carbon density in biomass and top soil stocks on Mediterranean woodlands - Héctor Hernández-Alonso; Jaime Madrigal-González; Lorién Tornos-Estupiña; Alberto Santiago-Rodríguez; Pilar Alonso-Rojo; Albert Morera-Beita; Fernando Silla (Plant and Soil, 2023)
Aims Carbon accumulation in terrestrial ecosystems is inherent to the vegetation development and ageing process. Primary productivity synthetize biomass which is constantly incorporated to soil. Vegetation community composition, and other ecological drivers, are known to mediate biomass production. However, links between forest developmental stage and ecological drivers of carbon stocks are unexplored. We address this topic under the prediction that species-rich and uneven-sized forests can improve carbon storage potential in biomass and topsoil fraction across its development. Methods The study was carried in forest stands growing under Mediterranean conditions in Central Spain. Carbon content in both above- and below-ground tree biomass and in topsoil organic matter (0–40 cm) was measured in 30 sampling plots of variable size (900–3000 m 2 ). We also assessed Shannon species diversity index, Gini tree-size inequality index and forest developmental stage using dendrochronological procedures to derive the mean age of the oldest trees. First-order interaction terms between diversity factors and forest age were regressed against carbon density in compartment-independent regressions. Results Forest-age and tree-size heterogeneity coupling was the main factor driving carbon density of both compartments. The interaction showed that woodlands maximize density in aged forests composed by uneven-sized trees. Models gave not support to consider species diversity as a mediator of carbon stocks. Conclusion Our results shed light on how tree-size heterogeneity can regulate the temporal dimension of forest ageing to rise the carbon storage potential. Mature forests in semi-arid environments cannot store carbon due to their intrinsic ontogeny, they need to grow structurally diverse.

Geologic framework of Cretaceous plutons along a west-to-east transect in the southern Peninsular Ranges batholith, Baja California, Mexico: Insights from geochemical, isotopic, and geochronologic data - Xochitl Guadalupe Torres-Carrillo; Luis Alberto Delgado-Argote; Bodo Weber; Manuel Contreras-López; Tomás Alejandro Peña-Alonso; Porfirio Avilez-Serrano; Doris Karina Gómez-Álvarez (International Geology Review, 2023)

Phytosociological analysis of the endemic Quercus faginea forests of the Iberian Peninsula - Alberto Luis Cantoral; Raquel Alonso-Redondo; Marta Eva García-González; Ángel Penas; Sara del Río (Plant Biosystems, 2023)

Bioaccumulation/bioconcentration of pharmaceutical active compounds in aquatic organisms: Assessment and factors database - María del Carmen Gómez-Regalado; Julia Martín; Juan Luis Santos; Irene Aparicio; Esteban Alonso; Alberto Zafra-Gómez (Science of The Total Environment, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

A comprehensive threat analysis to support the red list of marine and coastal ecosystems of Colombia - Edwin S. Uribe; Andrés Etter; Andrea Luna-Acosta; María Claudia Diazgranados; David Alonso; Luis Chasqui; Adriana Osorno; Alberto Acosta; Alexandra Rodríguez-Rodríguez; Constanza Ricaurte-Villota; Luisa Escobar; Alan Giraldo (Frontiers in Marine Science, 2022)
Introduction Human activities represent a growing threat to biodiversity, increasing species extinction and leading ecosystems to collapse. The knowledge of the spatial distribution of threats to ecosystems is fundamental to understanding their risk of collapse as defined by the Red List of Ecosystems, an International Union for Conservation of Nature (IUCN) global standard to guide conservation and management actions. Colombia is a megadiverse country; almost half of its territory is marine, and its ecosystems are subject to anthropogenic and climatic threats. Methodology This study provides a quantitative map assessment for a set of relevant anthropic and climatic threats and impacts on the marine and coastal areas of Colombia, intending to perform the threat description component of the Red List assessment protocol. A cumulative impact assessment was applied to analyze the threat levels (TLs) and impact levels of 12 anthropogenic and climatic pressures. Results The observed TL patterns meet spatial expectations, revealing that the assessment units in the Caribbean Sea are more threatened than those in the Pacific Ocean, and continental areas are more threatened than the oceanic ones. Habitat transformation and sea warming were the threats with the most impact on coastal and marine ecosystems, respectively. Climatic threats were widely extended throughout the study area, occurring even in the most pristine zones (e.g., Malpelo Island). Discussion Climate threats are challenging to national conservation strategies since these pressures are not completely manageable at local scales as they depend mainly on global efforts. Recommendations drawn from this work can guide actions for the conservation of the ecosystems of Colombia.

Same sensitivity with shorter exposure: behavior as an appropriate parameter to assess metal toxicity - Álvaro Alonso; Alberto Romero-Blanco (Ecotoxicology, 2022)
The exposure of animals to toxicants may cause a depletion in the energy uptake, which compromises reproduction and growth. Although both parameters are ecologically relevant, they usually need long-term bioassays. This is a handicap for the availability of toxicological data for environmental risk assessment. Short-term bioassays conducted with environmental concentrations, and using relevant ecological parameters sensitive to short-term exposures, such as behavior, could be a good alternative. Therefore, to include this parameter in the risk assessment procedures, it is relevant the comparison of its sensitivity with that of growth and reproduction bioassays. The study aim was the assessment of differences between endpoints based on mortality, behaviour, reproduction, and growth for the toxicity of metals on aquatic animals. We used the ECOTOX database to gather data to construct chemical toxicity distribution (CTD) curves. The mean concentrations, the mean exposure time, and the ratio between the mean concentration and the exposure time were compared among endpoints. Our results showed that behavioral, growth, and reproduction bioassays presented similar sensitivity. The shortest exposure was found in behavioral and reproduction bioassays. In general, the amount of toxicant used per time was lower in growth and reproduction bioassays than in behavioral and mortality bioassays. We can conclude that, for metal toxicity, behavioral bioassays are less time-consuming than growth bioassays. As the sensitivity of behavior was similar to that of growth and reproduction, this endpoint could be a better alternative to longer bioassays.

The zoophytophagous predator Pilophorus clavatus (Hemiptera: Miridae) induces plant defences in citrus - Meriem Dahmane; Alberto Urbaneja; Omar Ruíz-Rivero; Miquel Alonso-Valiente; Meritxell Pérez-Hedo (Journal of Pest Science, 2022)

Maximizing sexual signal transmission: use of multiple display sites by male houbara bustards - Juan C. Alonso; Inmaculada Abril-Colón; Carlos Palacín; Alberto Ucero; José M. Álvarez-Martínez (Behavioral Ecology and Sociobiology, 2022)
A good location of song or call posts and visual display sites of males is crucial for territory defence and mate attraction. These sites are typically located at prominent positions to ensure an efficient, long-distance sexual advertisement. If the purpose of display sites is to maximize visibility, a suitable strategy would be to use multiple display sites rather than just one site. We investigated this in the ground-displaying houbara bustard by using two recent technological advances that enabled us collecting high precision data, GSM/GPRS loggers provided with accelerometer and very high-resolution digital elevation models of the terrain. We found that 12 out of 20 marked males used two or three display sites instead of just one as previously assumed in this species. The most used display site had the largest viewshed and use of both alternative sites decreased in proportion to their decreasing viewsheds. The number of display sites was apparently determined by two factors. First, it was correlated with display intensity, suggesting that using multiple display sites may be a mechanism to increase sexual signal transmission in males that are dominant or in better condition. Second, supplementary display sites were not used when the principal display site already provided an excellent view of the surroundings, e.g. when it was located on a hilltop. These results confirmed that the function of secondary display sites is to supplement the viewshed provided by the principal display site, and so maximize sexual signal transmission. Significance statement Performing sexual display from just a single place is often not enough to reach all possible mates or competitors, so using multiple posts may be crucial for an effective sexual signal transmission. This is particularly important when the display is visual, and topographical barriers or vegetation may block the male’s line of view. Using last generation GSM/GPRS loggers equipped with accelerometers and very high-resolution digital elevation models of the terrain, we show how houbara bustard males, who perform a costly running display on the ground, have developed a complex display pattern that involves the use of various nearby display sites. These display sites are used in proportion to their visibilities, which shows that this multiple display site system has evolved to maximize the aggregated visual field of males and so increase their visibility to females and neighbour males.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Laboratory versus wild populations: the importance of population origin in aquatic ecotoxicology - Alberto Romero-Blanco; Álvaro Alonso (Environmental Science and Pollution Research, 2022)

Behavioral Variables to Assess the Toxicity of Unionized Ammonia in Aquatic Snails: Integrating Movement and Feeding Parameters - Álvaro Alonso; Gloria Gómez-de-Prado; Alberto Romero-Blanco (Archives of Environmental Contamination and Toxicology, 2022)
Behavioral endpoints are important parameters to assess the effects of toxicants on aquatic animals. These endpoints are useful in ecotoxicology because several toxicants modify the animal behavior, which may cause adverse effects at higher levels of ecological organization. However, for the development of new bioassays and for including the behavior in ecotoxicological risk assessment, the comparison of sensitivity between different behavioral endpoints is necessary. Additionally, some toxicants remain in aquatic environments for a few hours or days, which may lead to animal recovery after toxicant exposure. Our study aimed to assess the effect of unionized ammonia on the movement and feeding behaviors of the aquatic gastropod Potamopyrgus antipodarum (Tateidae, Mollusca) and its recovery after exposure. Four treatments were used: a control and three nominal concentrations of unionized ammonia (0.25, 0.5 and 1 mg N-NH 3 /L). Each treatment was replicated eight times, with six animals in each replicate. Animals were exposed to unionized ammonia for 48 h (exposure period) and, subsequently, to control water for 144 h (post-exposure period). Two movement variables were monitored without food and five feeding behavioral variables were monitored in the presence of food. Some of the feeding behavioral variables showed higher sensitivity (LOEC = 0.25–0.5 mg N-NH 3 /L) than the movement behavior variables monitored without food (LOEC = 1 mg N-NH 3 /L). After exposure to unionized ammonia, animals showed a recovery of most behavioral endpoints. The inclusion of post-exposure period and feeding behaviors in bioassays may make studies more realistic, which is crucial for a proper ecotoxicological risk assessment.

Emergence and spread of the potential variant of interest (VOI) B.1.1.519 of SARS-CoV-2 predominantly present in Mexico - Abril Paulina Rodríguez-Maldonado; Joel Armando Vázquez-Pérez; Alberto Cedro-Tanda; Blanca Taboada; Celia Boukadida; Claudia Wong-Arámbula; Tatiana Ernestina Nuñez-García; Natividad Cruz-Ortiz; Gisela Barrera-Badillo; Lucía Hernández-Rivas; Irma López-Martínez; Alfredo Mendoza-Vargas; et al. (Archives of Virology, 2021)

Assessment of the Effects of Environmental Concentrations of Microplastics on the Aquatic Snail Potamopyrgus antipodarum - Alberto Romero-Blanco; Adrián Remón-Elola; Álvaro Alonso (Water, Air, & Soil Pollution, 2021)
Microplastics are ubiquitous in aquatic ecosystems. They can be found at the surface, in the water column, and in sediments. Multiple negative impacts of microplastics on aquatic organisms have been reported, with most studies focusing on marine ecosystems. However, the effects of microplastics on freshwater ecosystems have been less studied, with a few studies focusing on benthic invertebrates. In this study, we exposed the New Zealand mud snail Potamopyrgus antipodarum (Gray, 1843) to an environmental range of concentrations of polystyrene microparticles (size range from 0.01 to 514 µm at 100, 500, and 1000 mg microplastics/kg dry weight (dw) of sediment) and two supra-environmental concentrations (2000 and 4000 mg/kg dw sediment). The impacts of the exposure to microplastics on mortality, behavior, and reproduction were assessed at long-term exposure (31 days). Mortality and reproduction were not significantly affected by microplastics. On the contrary, most of the microplastic treatments altered the behavior, causing a significant increase in reaction time compared with controls (0 mg microplastics/kg dw sediment). The highest concentration (4000 mg/kg) did not have an impact on the reaction time over the experimental period compared with controls. To our knowledge, this study is the first to assess the effects of microplastics on the behavior of the aquatic snail P. antipodarum . Our results showed that at environmental concentrations, the behavior of P. antipodarum was the most sensitive variable to the adverse effects of polystyrene microplastics.

Astragallus mollissimus plant extract: a strategy to reduce ruminal methanogenesis - Pedro Antonio Ochoa-García; Robin C. Anderson; Martha María Arévalos-Sánchez; Felipe Alonso Rodríguez-Almeida; Monserrath Félix-Portillo; Alberto Muro-Reyes; Aleksandar K. Božić; Claudio Arzola-Álvarez; Agustín Corral-Luna (Tropical Animal Health and Production, 2021)

Plant exposure to herbivore-induced plant volatiles: a sustainable approach through eliciting plant defenses - Meritxell Pérez-Hedo; Miquel Alonso-Valiente; Sandra Vacas; Carolina Gallego; Clara Pons; Vicent Arbona; José L. Rambla; Vicente Navarro-Llopis; Antonio Granell; Alberto Urbaneja (Journal of Pest Science, 2021)

Loss of Key Riparian Plant Species Impacts Stream Ecosystem Functioning - Alberto Alonso; Javier Pérez; Silvia Monroy; Naiara López-Rojo; Ana Basaguren; Jaime Bosch; Luz Boyero (Ecosystems, 2021)

Barks from avocado trees of different geographic locations have consistent microbial communities - Eneas Aguirre-von-Wobeser; Alexandro Alonso-Sánchez; Alfonso Méndez-Bravo; Luis Alberto Villanueva Espino; Frédérique Reverchon (Archives of Microbiology, 2021)

Antinociceptive and anti-inflammatory effects of Cuphea aequipetala Cav (Lythraceae) - Angel Josabad Alonso-Castro; Victor Arana-Argáez; Eunice Yáñez-Barrientos; Mario Alberto Ramírez-Camacho; Katarzyna Wrobel; Julio Cesar Torres-Romero; Carolina León-Callejas; Kazimierz Wrobel (Inflammopharmacology, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Characterization of cannonball jellyfish (Stomolophus sp. 2) blue protein: a pH-stable pigment - Raúl Balam Martínez-Pérez; Lourdes Mariana Díaz-Tenorio; Luis Alonso Leyva Soto; Pablo Gortáres-Moroyoqui; Leticia García-Rico; Jorge Alberto Rodríguez (Environmental Science and Pollution Research, 2020)

Herbicide biomonitoring in agricultural workers in Valle del Mayo, Sonora Mexico - Ana Paola Balderrama-Carmona; Melissa Valenzuela-Rincón; Luis Alberto Zamora-Álvarez; Norma Patricia Adan-Bante; Luis Alonso Leyva-Soto; Norma Patricia Silva-Beltrán; Edgar Felipe Morán-Palacio (Environmental Science and Pollution Research, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Anti-inflammatory and antinociceptive effects of an ethanol extract from Senna septemtrionalis - Víctor Ermilo Arana-Argáez; Fabiola Domínguez; Diego A. Moreno; Mario Alberto Isiordia-Espinoza; Julio Cesar Lara-Riegos; Emanuel Ceballos-Góngora; Juan Ramón Zapata-Morales; Lorenzo Franco-de la Torre; Sergio Sánchez-Enríquez; Angel Josabad Alonso-Castro (Inflammopharmacology, 2020)

Effects of litter mixing on litter decomposition and soil properties along simulated invasion gradients of non-native trees - Pilar Castro-Díez; Álvaro Alonso; Alberto Romero-Blanco (Plant and Soil, 2019)

Study on the removal of hormones from domestic wastewaters with lab-scale constructed wetlands with different substrates and flow directions - José Alberto Herrera-Melián; Rayco Guedes-Alonso; Alejandro Borreguero-Fabelo; José Juan Santana-Rodríguez; Zoraida Sosa-Ferrera (Environmental Science and Pollution Research, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Differences between 1999 and 2010 across the Falkland Plateau: fronts and water masses - M. Dolores Pérez-Hernández; Alonso Hernández-Guerra; Isis Comas-Rodríguez; Verónica M. Benítez-Barrios; Eugenio Fraile-Nuez; Josep L. Pelegrí; Alberto C. Naveira Garabato (Ocean Science, 2017)
Decadal differences in the Falkland Plateau are studied from the two full-depth hydrographic data collected during the ALBATROSS (April 1999) and MOC-Austral (February 2010) cruises. Differences in the upper 100 dbar are due to changes in the seasonal thermocline, as the ALBATROSS cruise took place in the austral fall and the MOC-Austral cruise in summer. The intermediate water masses seem to be very sensitive to the wind conditions existing in their formation area, showing cooling and freshening for the decade as a consequence of a higher Antarctic Intermediate Water (AAIW) contribution and of a decrease in the Subantarctic Mode Water (SAMW) stratum. The deeper layers do not exhibit any significant change in the water mass properties. The Subantarctic Front (SAF) in 1999 is observed at 52.2–54.8° W with a relative mass transport of 32.6 Sv. In contrast, the SAF gets wider in 2010, stretching from 51.1 to 57.2° W (the Falkland Islands), and weakening to 17.9 Sv. Changes in the SAF can be linked with the westerly winds and mainly affect the northward flow of Subantarctic Surface Water (SASW), SAMW and AAIW/Antarctic Surface Water (AASW). The Polar Front (PF) carries 24.9 Sv in 1999 (49.8–44.4° W), while in 2010 (49.9–49.2° W) it narrows and strengthens to 37.3 Sv.

Tree leaves of Salix babylonica extract as a natural anthelmintic for small-ruminant farms in a semiarid region in Mexico - Abdelfattah Z. M. Salem; Mona M. Y. Elghandour; Ahmed E. Kholif; Secundino López; Alberto B. Pliego; Moisés Cipriano-Salazar; Juan Carlos V. Chagoyán; Roberto Montes de Oca Jiménez; María U. Alonso (Agroforestry Systems, 2017)

Mélanges and other types of block-in-matrix formations in the Cantabrian Zone (Variscan Orogen, northwest Spain): origin and significance - Juan Luis Alonso; Alberto Marcos; Elisa Villa; Angela Súarez; Oscar Antonio Merino-Tomé; Luis Pedro Fernández (International Geology Review, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Diversity and pathogenicity of Colletotrichum species isolated from soursop in Colombia - Elizabeth Álvarez; Lederson Gañán; Alberto Rojas-Triviño; Juan F. Mejía; Germán A. Llano; Alonso González (European Journal of Plant Pathology, 2014)

Interethnic differences in UGT1A4 genetic polymorphisms between Mexican Mestizo and Spanish populations - Marisol López; Pedro Dorado; Alberto Ortega; Eva Peñas-Lledó; Nancy Monroy; Irma Silva-Zolezzi; Jesús Cobaleda; Alicia Gallego-Aguilera; María Elisa Alonso; Adrián LLerena (Molecular Biology Reports, 2013)

Sugar as nutritional supplement for the zoophytophagous predator Nesidiocoris tenuis - Pablo Urbaneja-Bernat; Miquel Alonso; Alejandro Tena; Karel Bolckmans; Alberto Urbaneja (BioControl, 2013)

Alcohol induces Golgi fragmentation in differentiated PC12 cells by deregulating Rab1-dependent ER-to-Golgi transport - Mónica Tomás; María Pilar Marín; Emma Martínez-Alonso; Guillermo Esteban-Pretel; Alberto Díaz-Ruiz; Rafael Vázquez-Martínez; María M. Malagón; Jaime Renau-Piqueras; José A. Martínez-Menárguez (Histochemistry and Cell Biology, 2012)

MEG Connectivity Analysis in Patients with Alzheimer’s Disease Using Cross Mutual Information and Spectral Coherence - Joan Francesc Alonso; Jesús Poza; Miguel Ángel Mañanas; Sergio Romero; Alberto Fernández; Roberto Hornero (Annals of Biomedical Engineering, 2011)

Valorization of Foundry Sand in Clay Bricks at Industrial Scale - Rebeca Alonso‐Santurde; Alberto Coz; Natalia Quijorna; Javier R. Viguri; Ana Andrés (Journal of Industrial Ecology, 2010)
Summary In this article, foundry sand as waste material has been valorized in ceramic brick manufacturing at industrial scale. The employment of a waste coming from one industry as an input for another is one of the key concepts of industrial ecology. To study the environmental behavior of the ceramic bodies in different life cycle stages, three leaching tests have been developed. We used an EN 12457 equilibrium leaching test with distilled water and a Wastewater Technology Centre acid neutralization capacity (WTC‐ANC) leaching test with different acidic leachates to carry out the environmental evaluation under different granular scenarios to ascertain the possibilities of the reuse or disposal of this granular material at the end of its useful life (end‐of‐life stage). Finally, we used a NEN 7345 diffusion leaching test for construction materials, with the aim of studying the environmental assessment at the use stage. Regulated pollutants in both stages have been evaluated. Furthermore, other soluble salts have been analyzed because they are closely related to the efflorescence phenomenon in bricks. Results indicate that core and green sand from the foundry industry can be used to replace clay content in construction materials, and that these foundry‐sand‐based ceramics improve some soluble salt results. Despite this fact, at the end‐of‐life stage in an inert waste landfill, lead, arsenic and chromium can be an environmental problem, both for commercial bricks and for foundry‐sand‐based bricks. This work can contribute to the determination of viability of sustainable processes of brick manufacturing that use foundry wastes as raw materials.

Fungi Isolated from Diseased Nursery Seedlings in Spain - Pablo Martín Pinto; Juan Alberto Pajares Alonso; Valentín Pando Fernández; Julio Javier Díez Casero (New Forests, 2006)

Kinetics of the Natural Evolution of Hydrogen Cyanide in Plants in Neotropical Pteridium arachnoideum and its Ecological Significance - Miguel E. Alonso-Amelot; Alberto Oliveros-Bastidas (Journal of Chemical Ecology, 2005)

Fishery and Ontogenetic Driven Changes in the Diet of the Spiny Dogfish, Squalus acanthias, in Patagonian Waters, Argentina - Mariano Koen Alonso; Enrique Alberto Crespo; Néstor Aníbal García; Susana Noemí Pedraza; Pablo Ariel Mariotti; Nancy Judith Mora (Environmental Biology of Fishes, 2002)

Distribution of volatile organic compounds in Madrid (Spain) - Rosa María Pérez-Pastor; Susana García-Alonso; Alberto José Quejido Cabezas (Environmental Science and Pollution Research, 1999)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Glucose and fructose consumption in a phosphoglucoseisomeraseless mutant in Saccharomyces cerevisiae - Carlos Pascual; Alberto Alonso; Celso Prez; Luis S. Herrera (Archives of Microbiology, 1979)